Oral application of probiotic, prebiotic, and synbiotic in Pacific white shrimp(Litopenaeus vannamei)challenged with Vibrio harveyi - Widanarni, .; Widagdo, Puguh; Wahjuningrum, Dinamella (Indonesian Society of Scientific Aquaculture (ISSA), 2012)
The use of antibiotics for controlling of luminous vibriosis caused by Vibrio harveyi is restricted now, because it induces antibiotic-resistant bacteria and leave residue in shrimp’s body. An alternative solution that can be done to treat the disease is by using applications of probiotic, prebiotic, and synbiotic. The aim of this research was to examine the effect of probiotic, prebiotic, and synbiotic on the survival rate and growth of Pacific white shrimp against V. harveyi infection. Feed as a treatment was supplemented with probiotic 1%, prebiotic 2%, and probiotic 1%+prebiotic 2% (synbiotic). Shrimps feed without supplementation of probiotic and prebiotic was used as a control treatment. The shrimps were maintainedin the aquarium (60×30×35 cm3) with a density of 40 shrimps/40 L and an average weight of 0.4±0.1 g. After 30 days of feeding treatment, the shrimp was challenged by immersion method with V. harveyi solution containing 106 CFU/mL. The results showed that before challenge, synbiotic feed treated shrimp has a growth rate (5.89%), feed conversionrate (1.21), and a high survival rate (80%). After challenge, survival rate (83.33%) of shrimp fed diet supplemented with synbiotic was higher than prebiotic (51.67%) and positive control (31.67%). Keywords: probiotic, prebiotic, synbiotic, Vibrio harveyi,Pacific white shrimp